Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region - Campelo, F.; Nabais, C.; García-González, I.; Cherubini, P.; GUTIÉRREZ, E.; Freitas, H. (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163doi: 10.1139/X09-163The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: climate reconstruction (PG); Dendrochronology; dendroclimatology; Quercus ilex

Relationships between climate and double rings in Quercus ilex from northeast Spain - Campelo, F.; GUTIÉRREZ, E.; Ribas, M.; Nabais, C.; Freitas, H. (Canadian Journal of Forest Research, 2007)
The influence of climatic factors on tree-ring width and the formation of double rings was studied in Quercus ilex L. growing in a coppice stand left unmanaged for 22 years. Ten trees were felled and discs were taken every 30 cm from bole and dominant branches. Dendrometer bands were installed on 10 nearby trees and the data recorded were used to confirm the accuracy of our tree-ring identification. They were also used to relate the seasonal radial growth pattern to double-ring formation. Double rings were frequent and occurred consistently along the stem. Two types of double rings could be recognized according to their width: type I, with the extra growth band accounting for approximately 50% of the tree ring; and type II, with a narrow extra growth band. Type I double rings were formed when approximately 1/2 of the growing-season precipitation occurred during the second growth period of the season and after the summer drought. Type II double rings occurred when approximately 1/3 of the precipitation in the growing season occurred after the summer drought. The formation of double rings was triggered by rainfall in summer and the extra growth-band width was related to summer and autumn environmental conditions. Double rings in Q. ilex can potentially be used in dendroclimatological studies, as they are formed in response to climatic conditions within the growing season.
doi: 10.1139/X07-050doi: 10.1139/X07-050The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: chronology (voyant); double rings; Drought; growth pattern; growth rings; Precipitation; Quercus ilex